Rapid Evidence Assessment (REA) of what works to improve educational outcomes for people with disabilities in Low- and Middle-Income Countries - Kuper, Hannah; Ashrita, Saran; White, Howard (Department for International Development (DFID), 2018)

Why do we care about evidence synthesis? An introduction to the special issue on systematic reviews - White, Howard; Waddington, Hugh (Journal of Development Effectiveness, 2012)
Systematic reviews are currently in high demand in international development. At least 100 new reviews are ongoing or already completed on a range of topics across the board in international development, many of which were commissioned by policy-making agencies. These new reviews need to be based on answerable questions, using methods of analysis and reporting which are appropriate for social and economic development programmes and relevant to users. This introductory paper lays out why we believe systematic reviews should be an important component of evidence-informed development policy and practice. It concludes by introducing the papers collected in this issue, which aim to demonstrate how reviews can be made to live up to the promises generated around them.
Keywords: -FullBiblioUHMLgen; -GeneralCitations; 3ie; CLL:en; Reviewed; impact evaluation; publicImportV1; systematic reviews

How to do a good systematic review of effects in international development: a tool kit - Waddington, Hugh; White, Howard; Snilstveit, Birte; Hombrados, Jorge Garcia; Vojtkova, Martina; Davies, Philip; Bhavsar, Ami; Eyers, John; Koehlmoos, Tracey Perez; Petticrew, Mark; Valentine, Jeffrey C.; Tugwell, Peter (Journal of Development Effectiveness, 2012)
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -missingHU; 3ie; DL4D cited; Reviewed; ___working_potential_duplicate; auto_merged; publicImportV1